1985
DOI: 10.1007/bf00392232
|View full text |Cite
|
Sign up to set email alerts
|

Induction of budding on chloronemata and caulonemata of the moss, Physcomitrella patens, using isopentenyladenine

Abstract: The bud-inducing effect of the cytokinin N(6)-(Δ(2)-isopentenyl)-adenine (i(6)-Ade) was examined in the moss Physcomitrella patens growing in liquid culture. Under these conditions, buds could be induced on chloronemata as well as on caulonemata. By application of i(6)-Ade, bud-formation was accelerated in both types of tissue. The number of buds, their size and their site of development were dependent on the concentration of the cytokinin in the range of 10(-7) M to 10(-5) M. Moreover, the percentage of caulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 15 publications
5
181
0
Order By: Relevance
“…Our results showed that BAP and KIN have a concentration-dependent effect on shoot bud induction in B. billarderi after six days of treatment, as was previously reported for the mosses Funaria hygrometrica [8,10,13] and P. patens [9]. BAP caused a higher response than KIN on bud induction, and the former favoured bud formation even at concentrations as small as 0.25 µM (Figure 1).…”
Section: The Effect Of Different Cytokinin Concentrations On the Indusupporting
confidence: 87%
See 1 more Smart Citation
“…Our results showed that BAP and KIN have a concentration-dependent effect on shoot bud induction in B. billarderi after six days of treatment, as was previously reported for the mosses Funaria hygrometrica [8,10,13] and P. patens [9]. BAP caused a higher response than KIN on bud induction, and the former favoured bud formation even at concentrations as small as 0.25 µM (Figure 1).…”
Section: The Effect Of Different Cytokinin Concentrations On the Indusupporting
confidence: 87%
“…The external application of cytokinins to mosses has been shown to favour the transition from filamentous protonemal tissue to gametophores by inducing shoot bud formation [8][9][10]. Further, in the moss Physcomitrella patens, it was reported that the energy growth status promotes protonemal cell differentiation; the high energy condition (addition of 150 mM glucose) favours the caulonema formation, whereas the low energy condition induces chloronema [11].…”
Section: Introductionmentioning
confidence: 99%
“…This electrolyte solution was composed of: Ca ( . Three types of solid media, namely MS (Murashige and Skoog 1962), BCD (Sabovljević et al 2009) and KNOP (Reski and Abel, 1985) , and 12000 mg L -1 of agar. Additionally, cultures on MS medium were assayed on half strength MS or supplemented with sucrose 15000 mg L -1 .…”
Section: Culture Media Assaysmentioning
confidence: 99%
“…The green microalga C. protothecoides FACHB-2 originally obtained from the Freshwater Algae Culture Collection of the Institute of Hydrobiology, Chinese Academy of Sciences, was cultured with light in KNOP medium (Reski et al, 1985). For autotrophic cultivation, it was inoculated in flask (250 mL) containing 100 mL medium, and cultured in 12 h:12 h light-dark cycle at a light intensity of 40 μmol/m 2 s. For heterotrophic cultivation, it was inoculated in medium containing 10 g/L glucose, and cultivated under darkness.…”
Section: The Strain and Cultivation Conditionsmentioning
confidence: 99%